Acid‐Base Interactions of Pyrazine, Ethyl Acetate, Di‐alcohols, and Lysine with the cyclic Alumosiloxane (Ph2SiO)8[Al(O)OH]4 in View of Mimicking Al2O3(H2O) Surface Reactions. Issue 22 (13th November 2020) - Veith, Michael; Kolano, David; Huch, Volker
Abstract : The etherate of (Ph2 SiO)8 [Al(O)OH]4 can be transformed into the pyrazine adduct (Ph2 SiO)8 [Al(O)OH]4 · 3N(C2 H2 )2 N (1 ), the ethyl acetate adduct (Ph2 SiO)8 [Al(O)OH]4 · 3H3 C‐C(O)OC2 H5 (2 ), the 1, 6‐hexane diol adduct (Ph2 SiO)8 [Al(O)OH]4 · 2HO–CH2 (CH2 )4 CH2 –OH (3 ) and the 1, 4‐cyclohexane diol adduct (Ph2 SiO)8 [Al(O)OH]4 · 4HO–CH(CH2 CH2 )2 CH–OH (4 ). In all compounds the OH groups of the starting material bind to the bases through O–H··· N (1 ) or O–H··· O hydrogen bonds (2, 3, 4 ) as found from single‐crystal X‐ray diffraction analyses. Whereas in 1 only three of the central OH groups bind to the pyrazines, in 2 two of them bind to the same carbonyl oxygen atom of the ethyl acetate resulting in an unprecedented O–H··· O··· H–O double hydrogen bridge. The hexane diol adduct 3 in the crystal forms a one‐dimensional coordination polymer with an intramolecularly to two OH groups grafted hexane diol loop, while the second hexane diol is connecting intermolecularly. In the cyclohexane diol adduct 4 all OH groups of the central Al4 (OH)4 ring bind to different diols, leaving one alcohol group per diol uncoordinated. These "free" OH groups form an (O‐H··· )4 assembly creating a three‐dimensional overall structure. When reacting with (Ph2 SiO)8 [Al(O)OH]4 lysine loses water, turns into the cyclic 3‐amino‐2‐azepanone, and transforms through chelation of one of the aluminum atoms the starting material into a new polycycle. The isolated compound has the composition (Ph2 SiO)12 [Al(O)OH]4 [Al2 O3 ]2 · 4 C6 H12 N2 O· 6(CH2 )4 O (5 ). Abstract :